The accounting students perception towards accounting professions - Setiawan Budi Ramadhan; Gunasti Hudiwinarsih (The Indonesian Accounting Review, 2015)
This study analyzed the perception of accounting students in various accounting profession by considering their characteristics during the courses taken before the end of the class. It aims to determine their profile in accounting. There are five employment sectors that can be registered by the accounting graduates, such as public accountants, management accountants, educator accountants, government accountants and ac-counting services office. It also analyzed their options for the accounting profession by considering the salary factor, professional training factors, professional recognition factor, factor of social values, work environment factors and consideration of the labor market. The data were collected using questionnaires directly distributed to them while they were still taking the courses of Accounting Seminar and Research Metho-dology with a sample of 117 respondents. The data were analyzed using descriptive analysis and methods of Crosstab. The results showed that there is a relationship be-tween age and choice of profession to the subject, and between the genders of choices of profession. Then the main factors considered by the students in the choice of account-ing profession is a factor of professional training, namely training before work, profes-sional recognition is an opportunity to thrive, salary and other salaries, labor market of career path length, work environment, namely pressure of work, and social values and the opportunity to interact with others.